Carbohydrate ingestion during prolonged high-intensity shuttle running in 30°C - Gant, N.; Stephenson, D.; Bullock, N.; Heames, K.; Williams, C. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Previous work examining high intensity intermittent shuttle running (Morris et al., 2003), suggested that exercise capacity is reduced in the heat (30°C) when a carbohydrate electrolyte solution (CE) is ingested, compared with an energy-free flavoured water (FW). Therefore, the aim of the present study was to examine the changes in deep body temperature, heart rate and sprint performance over 60min of exercise when ingesting these solutions. Methods Eleven male games players aged 23 ± 2 years with a mean body mass of 75 ± 11 kg and maximal oxygen uptake values of 58 ± 4 ml·kg-1·min-1, performed 60 min of a high intensity shuttle running protocol (Nicholas et al. 2000). This protocol involves 15 minute periods of exercise, consisting of repeated cycles of walking, sprinting, running and cruising at speeds set according to the participant`s O2 max. Subjects ingested 6.5 ml·kg-1 body mass of fluid before exercise and 3.5 ml·kg-1 during each 3 minute rest period separating exercise blocks. The fluid ingested was either a 6.4% carbohydrate-electrolyte solution (osmolality 288 mOsmol·kg-1; Na+ 21 mmol·l-1; K+ 0.56 mmol·l-1) or flavoured water (osmolality 45 mOsmol·kg-1; Na+ 6 mmol·l-1; K+ 0.08 mmol·l-1). Deep body temperature was measured using an ingestible telemetric sensor. Environmental temperature was 30.6 ± 0.1 °C and relative humidity was 31.8 ± 0.1 %. Drinks were administered in a double blind fashion; the treatment order was randomised and experimental trials were separated by 14 days of rest. Results Deep body temperature (Fig. 1) was higher during the CE trial (CE vs FW P<0.05). During the last minute of exercise they were 38.57 ± 0.1 °C and 38.34 ± 0.1 °C in the CE and FW trials respectively. Heart rate was higher during the CE trial (P< 0.05) compared with FW. During the last minute of exercise heart rates were 179 ± 6.4 beats·min-1, and 168 ± 8.9 beats·min-1 for the CE and FW trials respectively. Mean time taken to complete 15m maximal sprints (Fig. 2) was different between the two fluid conditions (P< 0.05), mean sprint time for each 15 minute period was less when ingesting the CE solution. There were no differences in plasma volume or perceived exertion between the trials. Discussion/Conclusion The higher core temperature observed when subjects ingested the CE beverage suggests that participants were under a greater thermal strain; these data provide some support for the observations of Morris et al. (2003). However, it appears that participants were working at a higher intensity during the sprinting phase of exercise when ingesting the CE solution. The added work performed may be responsible for some of the additional internal heat generated. It is also possible that different rates of gastric emptying of the two solutions may be responsible for alterations in the rate at which fluid losses are replaced and hence alter the dynamics of the thermoregulatory process. It appears that when ingesting the 6.4% CE solution subjects are able to sprint at a higher intensity, and offset the decline in sprint performance that occurs over time. Whether or not during further exercise the increased core temperature when ingesting the CE solution would ultimately lead to individuals reaching a performance limiting core temperature sooner when compared with FW is yet to be successfully addressed.